Steering motion control enhancement scheme of two wheeled wheelchair in confined space - Ahmad, Salmiah; Tokhi, M. Osman (Science and Engineering Publishing Company, 2013)
In this work, a cross compensator was augmented to an existing Fuzzy-Proportional Derivative (Fuzzy-PD) type controller developed for steering motion control of two-wheeled wheelchair. A two-wheeled wheelchair, which mimics a double inverted pendulum scenario, is a highly nonlinear system with strong coupling dynamics. Fuzzy-PD type controller was initially realised with some degree of steady state tracking error in steering maneouvre. The steady state error may be reduced by introducing integral action into the controller (Fuzzy-PID type). However, this will increase the fuzzy rule-base significantly, and thus the computational time will increase exponentially. Noting the strong coupling between Link1 and Link2 of the system, a cross compensator in the form of a proportional action is introduced to perform better steering motion of the two-wheeled wheelchair in a simpler manner keeping in mind the highly nonlinear, complex nature of the system. The compensator is augmented to the existing fuzzy-PD rules to reduce the steady state error in the steering motion. Preliminary results show significant improvement in steering motion angles of [-90° < ψ < 90°].